SAT0145 Long-Term Cost-Effectiveness Analysis of the Treatment with Infliximab, Etanercept and Adalimumab in Rheumatoid Arthritis Patients in Real-Life Clinical Practice. (9th June 2015) - Cárdenas, M.; de la Fuente, S.; Font-Ugalde, P.; Castro-Villegas, M.C.; Romero-Gόmez, M.; Ruiz-Vílchez, D.; Calvo-Gutiérrez, J.; Ortega-Castro, R.; Escudero-Contreras, A.; Casado, M.A.; Collantes, E.
Abstract : Background: Anti-tumour necrosis factor-α agents are effective in the management of rheumatoid arthritis (RA) patients, but superiority among them has not been established. Also, long-term pharmacoeconomic studies examining the cost-effectiveness of biological agents in real-life clinical practice are scarce. Objectives: To assess the efficiency, in terms of cost to achieve clinical remission (CR: DAS28 value<2.6), of the treatment with infliximab, etanercept and adalimumab in a real clinical setting after two years of treatment. Methods: All patients diagnosed of RA in a tertiary referral hospital attended through an interdisciplinary consensus protocol who started treatment with infliximab, etanercept or adalimumab between January 2007 and December 2012 were included. Data examined included demographic and clinical variables and use of direct health-care resources. Effectiveness was measured as the proportion of patients achieving CR after two years of treatment (DAS28 value<2, 6). Costs were assessed from the hospital perspective including the official drug acquisition costs and costs for diagnostic tests and different medical services, obtained from the Hospital's economic management database. Cost-effectiveness was calculated dividing total direct healthcare costs by percentage of patients achieving clinical remission. Results: 130 patients were included (55 on infliximab, 44 on etanercept and 31 on adalimumab). 45.20% of patients on adalimumab achieved clinical remission after two years, versus 29.1% on infliximab (p=0.133) and 22.7% on etanercept (p=0.040), with no significant differences between etanercept and adalimumab (p=0.475). Mean total health direct costs at two years were 29, 857.67 €, 25, 328.60 € and 23, 309.09 € for adalimumab, infliximab and etanercept, respectively. The mean cost (IC95%) to achieve CR after two years with adalimumab, infliximab and etanercept were 66, 057€ (48, 038-84, 076), 87, 040 € (78, 496-95, 584) and 102, 683€ (94, 559-110, 807) respectively. Adalimumab resulted more efficient than etanercept (p<0, 001) and infliximab (p=0, 026), without statistically significant differences between etanercept and infliximab (p=0.086). Conclusions: Adalimumab resulted the most efficient treatment to achieve clinical remission in patients with rheumatoid arthritis in real-life clinical practice conditions in our hospital during the period examined. Disclosure of Interest: None declared